(untitled) (Research, Society and Development, 2020)
This research reports a didactic experience in the National Program for Access to Technical Education and Prison Employment through the professional qualification course of Cleaning and Conservation Agent. It was observed that the prison system encompasses a reframed educational scenario in the modality of Youth and Adult Education (EJA). So that allows the prisoner to reintegrate into society. This paper aimed to describe the didactic and cognitive obstacles present in the EJA of the prison system, envisaging a didactic situation from an active methodological perspective. Didactic Engineering was adopted as the methodological course. Finally, it is possible to understand, in this context, the existence of didactic and cognitive obstacles that, despite hindering the teaching and learning process, do not prevent the realization of a potentially significant didactic situation for the students, such that a learning that develops have relevance in your life outside of school.